Answer:
(2)
Explanation:
Our logarithmic expression is:
.
Remember the logarithmic property that ln(a/b) = lna - lnb. So, we can write this as:
![ln((√(e) )/(y^3) )=ln(√(e) )-ln(y^3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/iomg8k3mtvd12pe5tij915itgkmglp4qef.png)
Also, we can write square roots as powers of one-half, so √e =
. There's another log property that:
. We can apply that here for both the √e and the y³:
![ln(√(e) )-ln(y^3)=(1)/(2) ln(e)-3ln(y)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7tsyg15vx4i8ki26fubobw75csr1si6ytc.png)
Finally, note that ln(e) is just 1, so we have:
![(1)/(2) ln(e)-3ln(y)=(1)/(2) -3ln(y)=(1-6ln(y))/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/bar3gz4rhll6rej1u5tr5ut6rxkyt4h721.png)
The answer is thus (2).
~ an aesthetics lover